A Novel biopolymer-based T. harzianum, (Th4d) - a viable alternative to chemical seed treatment for management of collar rot of groundnut: A Novel biopolymer-based T. harzianum, (Th4d) - a viable alternative to chemical seed treatment for management of collar rot of groundnut - S LAKSHMI PRASANNA; R D PRASAD; KSVP CHANDRIKA (Journal of Oilseeds Research, 2023)
Groundnut (Arachis hypogaea L.) is an economically important edible oil seed crop of the world. Collar rot caused by Aspergillus niger is one of the most serious, destructive diseases in groundnut. A field experiment on the effect of seed treatment with biopolymer-based T. harzianum, Th4d blend in groundnut on disease incidence and seed yield of groundnut was taken up at IIOR, Hyderabad during 2020 and 2021. Chitosan-based T. harzianum, Th4d blend recorded pooled mean of significantly high germination percent (90.0%), pod yield (3047 kg/ha) and reduced collar rot incidence (67.7%) whereas chemical seed treatment with carboxin + thiram recorded germination of 78%, 45.1% reduction in disease and 2064 kg/ha pod yield.